Rudolf Lenz’s Diccionario etimológico (1905-1910): a glottopolitical approach - Cáceres, Valentina; Ortiz, José Miguel; Rojas, Darío (Boletín de Filología, 2020)
From a glottopolitical approach (which assumes a close relationship between the construction of knowledge about language and power), we analyze published and unpublished materials that allow us to maintain that Rudolf Lenz’s Diccionario etimológico de voces chilenas derivadas de lenguas indígenas americanas (1905-1910), far from constituting a claiming gesture of Mapuzugun or the varieties of Castilian marked by contact with this language, is an organic part of the Chilean state’s project of colonization of the Araucanía and is therefore a tool at the service of the domination of the Mapuche people and the subaltern sectors of the nation. The Diccionario etimológico despite its descriptive posture that makes it stand out against the Chilean normativist lexicographic tradition of the 19th century, serves as a vehicle for an ideological representation of Chilean vulgar Castilian in terms of a difference conceived as a deficit, marked mainly by the influence of Mapuzugun. We extend the analysis of the dictionary text itself (particularly its preliminary sections) by examining two areas of the archive where the conditions of production and circulation of the work are manifested: the materials that point to its belonging in the investigations associated with the Society of Chilean Folklore and the reviews, letters and other documents that account for the reception that the Diccionario had in specialized circles.